1995
DOI: 10.1055/s-0038-1649959
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Low-Molecular Weight Heparin or Oral Anticoagulants for the Prevention of Deep-Vein Thrombosis in Elective Hip and Knee Replacement?

Abstract: SummaryObjective. To compare efficacy, safety, and feasibility of adjusted- dose oral anticoagulants (OAC) versus fixed-dose subcutaneous low molecular weight heparin (LMWH) for the prevention of deep venous thrombosis (DVT) in patients who have undergone elective hip or knee replacement.Design. Multicentre, single blind randomised trial. OAC (acenocoumarol, target International Normalised Ratio, 2.0-3.0) and LMWH (nadroparine, 60 aXa IU/kg once daily) were started preoperatively and continued for 10 days. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
2
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 27 publications
1
69
2
4
Order By: Relevance
“…The majority of trials had compared oral anticoagulation with LMWH (nine trials, [89][90][91][92][93][94][95][96]99 7260 patients), whereas the comparator was lowdose unfractionated heparin in four trials 82,85,87,97 among 382 patients ( Figure 19). Overall, an oral anticoagulant regimen appeared less effective than either an unfractionated or LMWH regimen for the prevention of DVT.…”
Section: Direct Comparison Of Oral Anticoagulants With a Heparin Regimenmentioning
confidence: 99%
“…The majority of trials had compared oral anticoagulation with LMWH (nine trials, [89][90][91][92][93][94][95][96]99 7260 patients), whereas the comparator was lowdose unfractionated heparin in four trials 82,85,87,97 among 382 patients ( Figure 19). Overall, an oral anticoagulant regimen appeared less effective than either an unfractionated or LMWH regimen for the prevention of DVT.…”
Section: Direct Comparison Of Oral Anticoagulants With a Heparin Regimenmentioning
confidence: 99%
“…Thromboprophylaxis in close proximity to hip arthroplasty, either preoperatively or postoperatively, may balance efficacy and safety to prevent thrombosis on one hand and bleeding on the other hand. Clinical observations indicated that LMWH at half the usual high-risk dose begun in close proximity to THA either preoperatively or postoperatively [39,40] was more effective than LMWH administered 12 hours preoperatively or 12-18 hours postoperatively [17,19]. However, administration less than 2 hours before surgery resulted in increased major bleeding, while a postoperative regimen of LMWH 4-6 hours after surgery provided efficacy without significantly increasing bleeding [40].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, it is recognized that deep vein thrombosis originates perioperatively and that preoperative prophylaxis may optimize antithrombotic effects [3][4][5][6][7]. Low-molecular-weight heparin (LMWH) is usually initiated 12 hours preoperatively [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In North America, LMWH proIn orthopaedic surgery, blood loss can be quite substantial.…”
Section: Introductionmentioning
confidence: 99%
“…How-ever, the unrestricted use of heparin as an antithrombotic agent is limited due to its various side effect, such as thrombocytopenia, osteoporosis, and hemorrhagic complications (Ockelford et al 1982, Carreras 1980, Mätzsch et al 1986). More recently, heparin has been gradually replaced by its low molecular weight derivative (less than 3,000 and ∼ 9,000, comparing to ∼ 13,000 of native heparin), obtained by partial fragmentation and fractionation of native heparin (Hamulyák et al 1995, Meyer et al 1995. Fragments below 16 to 20 monosaccharide units per heparin molecule (MW < 5, 000), while containing the specific pentasaccharide sequence essential for binding AT III, are not long enough to permit binding to thrombin; they therefore inhibit only activated factor X (Choay et al 1981).…”
Section: Antithrombotic Use Of Mammalian Glycosaminoglycansmentioning
confidence: 99%